Estimation of water budget component of Kosi river basin using SWAT model and high-resolution remote sensing data - Utkarsh Kumar; Dhirendra Kumar Singh; Murtaza Hasan; Nand Lal Kushwaha; Amrender Kumar; Abhishek M. Waghaye (Discover Geoscience)
Abstract It is essential to simulate and quantify the availability of water resources using hydrological model with reliable data. The current study successfully calibrated and validated the water balance of the Kosi River Basin using the Soil and Water Assessment Tool (SWAT) model. India Meteorological Department (IMD) daily gridded rainfall and monthly stream flow data were used to develop the model from 2000 to 2013. The model performed well with statistical value of Nash-Sutcliffe and correlation coefficient greater than 0.70 and 0.72 during calibration and 0.67 and 0.70 during validation respectively. The spatiotemporal variation of water budget component were estimated over study area. The result showed that approximately 35% of rainfall was lost by evapotranspiration to the rainfall received. The spatial variability map depicts that evapotranspiration loss was higher in northwestern region due to high vegetation. This study will enhance understanding of water budget component response on sparse rainguage network in hilly region of Uttarakhand. The study undertaken provides a reference framework for assessing water budgets in hilly regions with sparse rain gauge networks.